2014
DOI: 10.1137/130934258
|View full text |Cite
|
Sign up to set email alerts
|

A Model for the Operation of Perovskite Based Hybrid Solar Cells: Formulation, Analysis, and Comparison to Experiment

Abstract: Abstract. This work is concerned with the modeling of perovskite based hybrid solar cells formed by sandwiching a slab of organic lead halide perovskite (CH 3 NH 3 PbI 3−x Clx) photo-absorber between (n-type) acceptor and (p-type) donor materials-typically titanium dioxide and spiro. A model for the electrical behavior of these cells is formulated based on drift-diffusion equations for the motion of the charge carriers and Poisson's equation for the electric potential. It is closed by (i) internal interface co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
72
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(74 citation statements)
references
References 39 publications
2
72
0
Order By: Relevance
“…At the interface between the perovskite and the ETL, (1) the electron flux (and its associated current density) is conserved, (2) the hole flux (and its associated current density) is conserved, (3) there is no flux of halide ion vacancies, (4) and (5) both the electrostatic potential and electric displacement field are continuous, and (6) the majority carrier density (in this case the electrons) at the edge of the ETL is related to the neighbouring carrier density in the perovskite by a factor, k E , which depends upon the relevant band offset and change in effective density of states [11]. Therefore, at the interface between the ETL and the perovskite, the following conditions are applied…”
Section: Continuity Conditions On the Interfaces (X = 0 And X = B)mentioning
confidence: 99%
See 1 more Smart Citation
“…At the interface between the perovskite and the ETL, (1) the electron flux (and its associated current density) is conserved, (2) the hole flux (and its associated current density) is conserved, (3) there is no flux of halide ion vacancies, (4) and (5) both the electrostatic potential and electric displacement field are continuous, and (6) the majority carrier density (in this case the electrons) at the edge of the ETL is related to the neighbouring carrier density in the perovskite by a factor, k E , which depends upon the relevant band offset and change in effective density of states [11]. Therefore, at the interface between the ETL and the perovskite, the following conditions are applied…”
Section: Continuity Conditions On the Interfaces (X = 0 And X = B)mentioning
confidence: 99%
“…Due to the existence of mobile ion vacancies, the perovskite layer must be treated as a mixed ionic-electronic conductor for the purpose of device simulation. The first works [2,11,25] to apply numerical methods to PSC modelling reported that their simulations suffered from prohibitively long calculation times and inaccuracies in solution for realistic values of the parameters. A combined analytic/numerical method was used by Richardson et al [5,18] to reveal how iodide ion vacancies accumulate/deplete in very narrow layers (called Debye layers) adjacent to the perovskite boundaries.…”
Section: Introductionmentioning
confidence: 99%
“…This section provides the detailed understanding of the charge generation and recombination processes within a perovskite solar cell. Sun et al 32 [35][36][37][38] . With both the analytical and the numerical model, the total generation of charges is obtained by the integration of the locally-generated charges over the whole absorber layer thickness.…”
Section: Si-1 Analytical Model Of the Perovskite Pin-type Solar Cellsmentioning
confidence: 99%
“…Dissipativity and convergence to the thermal equilibrium for large time have also been established for this generalized model [26]. Let us underline that more recently, driven by applications like organic semiconductors, there is an increased interest in drift-diffusion models with arbitrary statistical distribution functions [11,40].…”
Section: Introductionmentioning
confidence: 99%